Žaһandyķ syn-ķaterler ža̋ne ruchani ķauìpsizdìk = Globalʹnye vyzovy i duchovnaja bezopasnostʹ - Beysenov, B. K. (Chabaršy. Dintanu serijasy, 2015)
In this article are considered the principles of globalization world’s threats which are conducted against a human civilization. Congress of leaders of world and traditional religions plays an important role in ensuring stability in the world as interfaith consent, tolerance and integration of dialogue between cultures and civilizations. Congress of leaders of world and traditional religions is important in development of dialogue and trust values. The author of article during the analysis of interrelation of the state and religion tried to explain relationship of secularity and religiousness.